No evidence for an association between facial fluctuating asymmetry and vocal attractiveness in men or women. (29th June 2020) - Kordsmeyer, Tobias L.; Thies, Yasmin T. K.; Ekrami, Omid; Stern, Julia; Schild, Christoph; Spoiala, Cristina; Claes, Peter; Van Dongen, Stefan; Penke, Lars
Abstract: Abstract: Facial fluctuating asymmetry (FA), presumably a proxy measure of developmental instability, has been proposed to inversely relate to vocal attractiveness, which may convey information on heritable fitness benefits. Using an improved method of measuring facial FA, we sought to replicate two recent studies that showed an inverse correlation of facial FA with vocal attractiveness. In two samples of men ( N = 165) and women ( N = 157), we investigated the association of automatically measured facial FA based on 3D face scans with male and female observer-rated attractiveness of voice recordings. No significant associations were found for men or women, also when controlling for facial attractiveness, age, and body mass index. Equivalence tests show that effect sizes were significantly smaller than previous meta-analytic effects, providing robust evidence against a link of facial FA with vocal attractiveness. Thus, our study contradicts earlier findings that vocal attractiveness may signal genetic quality in humans via an association with FA.